Contrasting soil temperature regimes in peatlands of the discontinuous permafrost zone (Western Siberia) - Tatiana V. Raudina; Sergey V. Loiko; Georgyi I. Istigechev; Sergey P. Kulizhskiy; Laurent Orgogozo; Oleg S. Pokrovsky (Geoderma)
Carbon cycling in permafrost peatlands is strongly influenced by both hydrology and temperature and is closely linked to microtopography. In this study, we assessed soil temperature regimes in the sporadic permafrost zone of Western Siberia, one of the most climate-sensitive regions currently undergoing dramatic changes. Based on topographic mapping, photogrammetry, soil, vegetation and thermometric observations, we related the soil thermal regimes of the dominant peatland’s landforms to snow cover, water pathways, peat thickness and ground vegetation. In flat-mound peatland complex, thick peat deposits and convex forms (local elevations) induced a small accumulation of snow in winter, which led to coldest temperatures on the peat plateaus. The peat plateau soils with a thin peat layer and similar lichen-shrub vegetation had three time thicker active layer. Soils in adjacent sedge-Sphagnum fens remained noticeably cooler in summer but warmer in winter due to the insulating effect of thick snow cover. In contrast, soils in drained basins of thermokarst lakes froze to a shallower depth due to the absence of peat and the efficient insulation provided by thick snow retained on tall sedges. Overall, even within a small peatland complex in Western Siberia, soil temperature regimes can vary significantly over just a few hundred meters, resembling differences typically observed across distinct climatic zones. With ongoing climate warming, the active layer thickness is expected to increase, leading to a greater accumulation of suprapermafrost water, with maximum expansion occurring in the peripheral zones of the peatland.